Schopenhauer’s Philosophy of Law in Carl Schmitt’s debate with Erich Jung (1912-1913) - del Estal Sánchez, Héctor (Res Publica. Revista de Historia de las Ideas Políticas, 2020)
The aim of this essay is to offer coherently the significance and meaning of Carl Schmitt’s polemical article Schopenhauer’s Philosophy of Law Outside his Philosophical System (1913) as response to Erich Jung’s Das Problem des natürlichen Rechts (1912). Firstly, we present a contextualized overall picture of this last work as paying attention to its debts with the philosophy of law of Arthur Schopenhauer, and then we present the arguments put forward by Carl Schmitt in that text, and finally we show what were the features Schmittian thought on those years in order to highlight its philosophical significance as an attack to Junguian-Schopenhauerian technification of law and State.
Keywords: Carl Schmitt; Arthur Schopenhauer; Erich Jung; Natural Law; Legal Positivism